Policing Models of Indonesian National Police, Royal Thai Force, and Philippine National Police: A Comparative Study - Sukarman Sukarman; Erlangga Teja Wastika (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Policing is one of the most important of the functions undertaken by every sovereign government. For the state machinery, police is an inevitable organ which would ensure maintenance of law and order, and also the first link in the criminal justice system. On the other hand, for common man, police force is a symbol of coercive force of authority and at the same time, the protector from crime. Police men get an institution identity from the uniform they wear; the common man identifies, distinguishes, and awes him on account of the same uniform. The police systems in Association of South East Asian Nations, especially in Indonesia, Thailand, and Philippines have developed on a socio-cultural background, and for this reason alone huge differences exist between these police systems. From the singular coordinated centralized system of police in Indonesia organized under the president to the odd police forces that exist in Philippines, policing mainly rests on either of the two broad principles: (1) policing by consent and (2) policing by law. This paper tries to examine the various police systems that exist in the world, taking Indonesia, Thailand, and Philippines as examples of various types of policing models. The paper takes cue from these systems, their positives, negatives, and tries to find out how the indonesia system, can be understood in the light of these policing models.